2013
DOI: 10.1016/j.bbamem.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid induces opening of connexin26 hemichannels through a PI3K/Akt/Ca2+-dependent pathway

Abstract: Connexin hemichannel (Cx HC) opening is involved in physiological and pathological processes, allowing the cellular release of autocrine/paracrine signaling molecules. Linoleic acid (LA) is known to modulate the functional state of connexin46 (Cx46) HCs. However, the molecular mechanism involved in this effect, or whether LA affects HCs constituted of other connexins, remains unknown. Here, we report the effects of LA on HCs in HeLa cells that express Cx26, one of the main Cxs in the cochlear sensory epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Using a different experimental approach to deplete intracellular ATP consisting in hypoxia, nutrient deprivation, high K + and acidic pH to mimic the extracellular milieu of ischemic cells, our results showed that Akt-mediated regulation of Cx43 HCs was also present in this experimental model. Considering that linoleic acid, a pro-inflammatory unsaturated fatty acid, also increase Cx43 HC activity by a Ca 2+/ Akt dependent pathway [29], we propose that this mechanism is activated in general inflammatory states regardless the stimuli. Considering our results and those reported previously, Akt-dependent regulation of Cx43 HCs and gap junctions seems to be a general mechanism operating in physiological (mechanic stress) [26] as well as pathologic conditions (hypoxia/reoxygenation, MI) [25,45], but further experiments should be done to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a different experimental approach to deplete intracellular ATP consisting in hypoxia, nutrient deprivation, high K + and acidic pH to mimic the extracellular milieu of ischemic cells, our results showed that Akt-mediated regulation of Cx43 HCs was also present in this experimental model. Considering that linoleic acid, a pro-inflammatory unsaturated fatty acid, also increase Cx43 HC activity by a Ca 2+/ Akt dependent pathway [29], we propose that this mechanism is activated in general inflammatory states regardless the stimuli. Considering our results and those reported previously, Akt-dependent regulation of Cx43 HCs and gap junctions seems to be a general mechanism operating in physiological (mechanic stress) [26] as well as pathologic conditions (hypoxia/reoxygenation, MI) [25,45], but further experiments should be done to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Images were acquired by using an Olympus BX 51W1I upright microscope and the imaging system described above. Data were recorded every 1 min and analyzed with METAFLUOR software (Universal Imaging, Downingtown, PA) as described previously [29]. For experiments with Akti, cells were first incubated for 30 min with 10 μM Akti and then loaded with Fura2 by incubating them for additional 30 min in saline solution containing 5 μM Fura2-AM.…”
Section: Methodsmentioning
confidence: 99%
“…CaM was recognized to play a critical role in regulating gap junction channels by uncoupling gap junction channels and inhibiting gap junction permeability (19). Although extracellular Ca 2+ inhibits hemichannel opening, intracellular Ca 2+ is reported to positively regulate Cx43 and Cx32 hemichannel activity (20)(21)(22). Additionally, increased intracellular Ca 2+ enhances the electrical conductance of Cx46 hemichannels, contrary to the reduced gap junction channels (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although extracellular Ca 2+ inhibits hemichannel opening, intracellular Ca 2+ is reported to positively regulate Cx43 and Cx32 hemichannel activity (20)(21)(22). Additionally, increased intracellular Ca 2+ enhances the electrical conductance of Cx46 hemichannels, contrary to the reduced gap junction channels (20). Concurring with our finding, another paper reports that G45 residue in Cx26 is a Ca 2+ sensor and mutation of this residue to E in the Keratitisichthyosis-deafness (KID) syndrome leads to "leaky" hemichannels and cell death (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, knowledge about the regulation of HCs (or GJCs) by FFAs in the epithelium of the gastrointestinal tract is very limited and is incompletely understood in other cell types [21-24]. …”
Section: Introductionmentioning
confidence: 99%